Two new Ni/Co-MOFs as electrocatalysts for the oxygen evolution reaction in alkaline electrolytes. (26th September 2022) - Yan, Yang-Tian; Ge, Lei; Wu, Yun-Long; Cai, Wei; Tang, Peng-Fei; Zhang, Wen-Yan; Wang, Yao-Yu
Abstract : Two novel Ni/Co-MOFs electrocatalysts were synthesized. Ni-MOF demonstrated a good activity in electrocatalytic OER performances and short-term electrochemical durability. Abstract : The development of non-noble metal electrocatalysts with excellent performance is very important for the oxidation of water in alkaline media. Metal–organic frameworks (MOFs) have recently emerged as potential catalysts for a variety of reactions due to their atomically dispersed metal centers and accessible active sites. In this work, we report the synthesis of two new Ni-MOF and Co-MOF, [Ni(H2 L-NO2 )(H2 O)3 ] n (1 ) and [Co(H2 L-NO2 )(H2 O)3 ] n (2 ), as oxygen evolution reaction electrocatalysts. Ni-MOF and Co-MOF demonstrated a good activity with an overpotential of 355 mV and 394 mV to drive a geometrical catalytic current density of 10 mA cm −2 in 1.0 M KOH, transcending the performance of the noble OER catalyst, RuO2 . The OER mass activity of Ni-MOF is 1.6 and 3.8 times that of RuO2 and Co-MOF at an overpotential of 350 mV. Moreover, stability tests indicate that these two catalysts demonstrate short-term electrochemical durability.